A Natural Fit: Exploring Business-Owning Families’ Antecedents and Approaches to Impact Investing and Social Venturing - Roche, Jeanne (IE University, 2025)
This dissertation examines the engagement of business-owning families and their members in the fields of impact investing and social venturing, and contributes to three key areas. First, it advances family business scholarship by extending the study of business-owning families beyond the boundaries of the family firm. It highlights their heterogeneous engagement in social endeavors, offering a nuanced understanding of how they balance a hybridity of objectives, both financial and non-financial, based on their unique frame of reference. Second, it contributes to entrepreneurship research by shedding light on how individuals construct entrepreneurial identities in nascent and ambiguous fields such as impact investing, and how they may use their family as a salient social referent to guide their identity construction. Third, it provides new insights into social entrepreneurship and cross-sector collaborations by examining the case of a social enterprise selling the majority of its shares to a large family group. The study identifies how both entities were integrated in ways that helped sustain social impact post-acquisition, informing both scholars and practitioners on structuring mission-driven partnerships. By integrating these perspectives, this dissertation deepens our understanding of business-owning families’ social behaviors, the crafting of entrepreneurial identity in new fields, and the conditions under which social enterprises can maintain their purpose in cross-sector partnerships.
Un encaje natural: Exploración de los antecedentes y enfoques de las familias empresarias en la inversión de impacto y el empredimiento social
Esta tesis examina la participación de las familias empresarias y sus miembros en los ámbitos de la inversión de impacto y el emprendimiento social, y contribuye a tres áreas clave. En primer lugar, avanza en la investigación sobre empresas familiares al ampliar el estudio de las familias empresarias más allá de los límites de la empresa familiar. Destaca su participación heterogénea en iniciativas sociales, ofreciendo una comprensión matizada de cómo equilibran una hibridación de objetivos, tanto financieros como no financieros, en función de su marco de referencia único. En segundo lugar, contribuye a la investigación en emprendimiento al indagar sobre cómo los individuos construyen identidades emprendedoras en campos emergentes y ambiguos, como la inversión de impacto, y cómo pueden utilizar a su familia como un referente social relevante para orientar dicha construcción identitaria. En tercer lugar, proporciona nuevas perspectivas sobre el emprendimiento social y las colaboraciones intersectoriales al examinar el caso de una empresa social que vende la mayoría de sus acciones a un grupo empresarial familiar de gran tamaño. El estudio identifica decisiones y medidas clave que ayudan a sostener el impacto social tras la adquisición, proporcionando información tanto a académicos como a profesionales sobre la estructuración de asociaciones orientadas a la misión social. Al integrar estas perspectivas, esta tesis profundiza en la comprensión del comportamiento social de las familias empresarias, la construcción de la identidad emprendedora en nuevos campos y las condiciones bajo las cuales las empresas sociales pueden mantener su propósito en asociaciones intersectoriales.